Is There Any Relationship Between Biochemical Indices and Anthropometric Measurements With Dorsolateral Prefrontal Cortex Activation Among Older Adults With Mild Cognitive Impairment? - You, Yee Xing; Shahar, Suzana; Mohamad, Mazlyfarina; Rajab, Nor Fadilah; Che Din, Normah; Lau, Hui Jin; Abdul Hamid, Hamzaini (Frontiers in Human Neuroscience, 2022)
Working memory is developed in one region of the brain called dorsolateral prefrontal cortex (DLPFC). A dysfunction of this region leads to synaptic neuroplasticity impairment. It has been reported that several biochemical parameters and anthropometry play a vital role in cognition and brain health. This study aimed to investigate the relationships between cognitive function, serum biochemical profile and anthropometry with DLPFC activation. A cross-sectional study was conducted among 35 older adults (≥60 years) who experienced MCI. For this purpose, we distributed a comprehensive interview-based questionnaire for collecting sociodemographic information from the participants and conducting cognitive tests. Anthropometry was measured and fasting blood specimens were collected. We investigated their brain activation using the task-based fMRI(N-back), specifically in the DLPFC region. Positive relationships were observed between brain derived neurotrophic factor (β=0.494, p<0.01), and mini-mental state examination (β=0.698, p<0.01), however negative relationships were observed between serum triglyceride (β= -0.402, p<0.05) and serum malondialdehyde (β= -0.326, p<0.05) with right DLPFC activation (R2=0.512) while the participants performed 1-back task after adjustments for age, gender and years of education. In conclusion, higher serum triglycerides, higher oxidative stress and lower neurotrophic factor were associated with lower right DLPFC activation among older adults with MCI. A further investigation needs to be carried out to understand the causal-effect mechanisms of the significant parameters and the DLPFC activation so that better intervention strategies can be developed for reducing the risk of irreversible neurodegenerative diseases among older adults with MCI.